Bioversity International financial statements 2013: for the year ended December 31, 2013: auditor’s report - Bioversity International (Bioversity International, 2014)
Bioversity International’s financial mandate includes maintaining accountability and transparency in its finances, and to evaluate and communicate direct impact from our work to our donors, partners and the wider research and development community. Bioversity International is also developing networks and strategic alliances to maximise private sector funding and partnership opportunities.